Enhancing students’ thinking skills: the use of real-world context in the problem solving method in the Islamic and Asian civilization course - Nor Hanani Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Thinking skill is one of the skills that students are expected to have, particularly students of higher education. One of the compulsory courses that the Malaysian higher education students need to complete during their undergraduate study is the Islamic and Asian Civilization (TITAS) course. This course is made compulsory by the Malaysian Ministry of Education and it aims to provide students with the understanding of various elements of civilization and the implication of this course to national development. The course also aims to produce students who are able to relate civilization with current societal issues. In an observation that the researcher made on a group of 97 students who completed this course in 2017, the researcher found that most of these students have not been able to relate TITAS with current issues that the country is grappling with. Similar observation was made by Mustapha Kamal Ahmad Kassim who wrote that although the course is vital, most students have not been able to master most of the course content. The students’ failure to understand the content is visible through the way the students articulate their ideas in their written assignments and verbal presentations that are usually assessed in the course. The research found that the problem solving method as a teaching and learning method is able to enhance students’ thinking skills. The main question is, how does the use of problem solving method, specifically the use of today’s real-world context, in the teaching and learning of civilization concepts in the TITAS course enhance students’ thinking skills? To what extent is problem solving method effective in enhancing thinking skills through the use of real-world context when the concepts of civilization are taught to students through this method? Having these questions in mind, this study seeks to fulfil two main objectives. Firstly, to examine and improve the use of problem solving method, specifically the use of today’s real-world context, in the teaching and learning of civilization concepts in the TITAS course. Secondly, to examine the effectiveness of the use of the problem solving method, specifically the use of real-world context, in the teaching and learning of civilization concepts in the TITAS course, in enhancing thinking skills. Data were obtained through observation and documentation. Observations, aided by the use of checklists were carried out during the students’ presentations. The students’ written reflections were analysed through content analysis. Three action research processes were identified during the application of the problem solving method. The research also identified the effectiveness of the use of problem solving method, specifically the use of real-world context, in the teaching and learning of civilization concepts in the TITAS course. It was a matter to attempt and to stimulate students understanding to make problem solving as a way for knowledge acquisition and developing cognitive abilities in terms of reasoning, critical thinking, problem solving and decision making.